Dynein light chain 1 regulates dynamin-mediated F-actin assembly during sperm individualization in Drosophila. - Ghosh-Roy, A.; Desai, B.S.; Ray, K. (Molecular Biology of the Cell, 2005)
Toward the end of spermiogenesis, spermatid nuclei are compacted and the clonally related spermatids individualize to become mature and active sperm. Studies in Drosophila showed that caudal end-directed movement of a microfilament-rich structure, called investment cone, expels the cytoplasmic contents of individual spermatids. F-actin dynamics plays an important role in this process. Here we report that the dynein light chain 1 (DLC1) of Drosophila is involved in two separate cellular processes during sperm individualization. It is enriched around spermatid nuclei during postelongation stages and plays an important role in the dynein-dynactin-dependent rostral retention of the nuclei during this period. In addition, DDLC1 colocalizes with dynamin along investment cones and regulates F-actin assembly at this organelle by retaining dynamin along the cones. Interestingly, we found that this process does not require the other subunits of cytoplasmic dynein-dynactin complex. Altogether, these observations suggest that DLC1 could independently regulate multiple cellular functions and established a novel role of this protein in F-actin assembly in Drosophila.